The relationship between learning style, teachers personality and academic performance of gifted underachieving students in Nigeria (2015)
This paper examines the relationship between learning style, teachers' personality and academic performance of gifted underachieving students. Education is a continuing process to develop an individual's potential towards academic performance with various skills that are holistic and integrated. Gifted underachieving students may not believe that they can do well. A lack of confidence in their skills inhibits them from attempting tasks in which they do not believe they can succeed, therefore this study examines the causes of underachievement as well as characteristics of gifted underachievers as they may seem rebellious, show marked hostility towards adult figures and general distrust of adults among others. In addition, the influence that learning style and teachers' personality have on academic performance of gifted underachieving students were discussed as well as meaning and concept of variables of interest such as gifted underachievers, learning styles, teachers' personality and academic performance. It was concluded that if unchallenging scholastic environments produce underachieving gifted students, then providing intellectual challenge and stimulation at all grade levels should decrease underachievement. Finally, it was recommended that teachers should design teaching and learning methods that are best suited for the individual style of each student. Furthermore, students' thinking style should be included in the teacher education programme. Such knowledge will enable teachers to develop effective teaching methods and pedagogical strategies to respond to the diverse thinking styles of students in science classroom.